Joyful School, Empowered Students: Students' Interest and Talent Development Through Extracurricular at Mataram 24 Elementary School - Prayogi Dwina Angga; Nurwahidah Nurwahidah; I Putu Herry Widhi Andika; Irwandi Putra Ramli; Endiyah Sukesiningsih (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2026)
Extracurricular activities are a strategic instrument for holistically developing student potential, but their implementation in elementary schools is often not optimal. The purpose of this community service activity is to develop and strengthen extracurricular services based on student interests and talents at Mataram 24 Elementary School. This community service activity is carried out in three main stages, namely: (1) planning through observation, interest mapping, and Focus Group Discussion (FGD); (2) implementation of extracurricular programs; and (3) evaluation of activity results. There are three types of extracurricular activities facilitated by referring to the planning results, namely Tahfidz, Paskibra, and English Club. Community service activities show an increase in student participation and involvement. The Tahfidz extracurricular activity shows a significant contribution to Al-Quran literacy, Paskibra strengthens discipline and cooperation, while English Club can improve self-confidence and basic English communication skills. In addition to its direct impact on students, this activity also helps schools in systematically designing and managing extracurricular activities. The results of this activity also strengthen collaboration between universities and schools to revitalize the function of extracurricular activities as a vital tool for developing the character and potential of elementary school students. This program also has the potential to become a model for good practice in strengthening self-development services in elementary schools.